Complement factor D haplodeficiency is associated with a reduced complement activation speed and diminished bacterial killing - Langereis, Jeroen D (Clin Transl Immunology, 2021)
OBJECTIVES: Complete deficiency of alternative pathway (AP) complement factors, explained by homozygous mutations, is a well‐known risk factor for invasive bacterial infections; however, this is less obvious for heterozygous mutations. We describe two siblings with a heterozygous NM_001928.3(CFD):c.125C>A p.(Ser42*) mutation in the complement factor D (fD) gene having a history of recurrent bacterial infections. We determined the effect of heterozygous fD deficiency on AP complement activity. METHODS: We determined the effect of fD levels on complement activation as measured by AP activity, complement C3 binding to the bacterial surface of Neisseria meningitidis (Nm), Streptococcus pneumoniae (Sp) and non‐typeable Haemophilus influenzae (NTHi), and complement‐mediated killing of Nm and NTHi. In addition, we measured the effect of vaccination of complement C3 binding to the bacterial surface and killing of Nm. RESULTS: Reconstitution of fD‐deficient serum with fD increased AP activity in a dose‐ and time‐dependent way. Reconstitution of patient serum with fD to normal levels increased complement C3 binding to Sp, Nm and NTHi, as well as complement‐mediated killing of Nm and NTHi. Vaccination increased complement C3 binding and resulted in complete killing of Nm without fD reconstitution. CONCLUSION: We conclude that low fD serum levels (< 0.5 μg mL(−1)) lead to a reduced speed of complement activation, which results in diminished bacterial killing, consistent with recurrent bacterial infections observed in our index patients. Specific antibodies induced by vaccination are able to overcome the diminished bacterial killing capacity in patients with low fD levels.